Distinct forest bird communities are strongly associated with red spruce-northern hardwood ecosystems in Central Appalachia, USA. (February 2022) - Clipp, Hannah L.; Brown, Donald J.; Rota, Christopher T.; Wood, Petra B.
Graphical abstract: Highlights: Avian community may be a valuable indicator of red spruce forest integrity. Red spruce and northern hardwood forest types had distinct bird communities. Indicator species analyses identified 11 species associated with red spruce forest. Forest type and red spruce cover influenced bird communities more than size class. Abstract: Degraded red spruce ( Picea rubens )-northern hardwood ecosystems are the focus of restoration efforts across high-elevation landscapes in the Central Appalachian region of the eastern United States. To promote ecosystem function and long-term sustainability of restored forests, it is important to understand the associated biota, including bird communities. Certain bird species could serve as ecological indicators, with potential applications for evaluating restoration efforts. However, contemporary and statistically rigorous studies of red spruce bird communities in this region are lacking, as is a formal analysis of indicator species. The purpose of this study was to use multivariate regression trees and indicator species analyses to determine if bird communities and individual bird species, respectively, are strongly associated with the red spruce-northern hardwood ecosystem in Central Appalachia. Specifically, we assessed those associations with three distinct but complementary sets of forest characteristics, focusing on (1) red spruce and northern hardwood forest types, (2) classes of percent red spruce cover, and (3) red spruce and northern hardwood stand size classes. Community-wide avian point count survey data were collected in mid-May to mid-July 2010–2019 at 645 sampling points located in forest stands throughout the Monongahela National Forest in West Virginia. We found that red spruce and northern hardwood forest types had distinct bird communities within the study area, and that community composition differed among red spruce cover classes. In addition, forest type was more influential on bird community composition than stand size class (poletimber or sawtimber). Eleven indicator species were consistently associated with red spruce forests, whereas fewer species were identified as indicator species for northern hardwood forests. Ultimately, the distinctiveness of the bird community in red spruce forests and strength of those associations highlight the critical need for and importance of restoration efforts targeting red spruce-northern hardwood ecosystems in the Central Appalachians to ensure long-term maintenance of regional avian diversity.